2015
DOI: 10.1098/rspb.2015.1351
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal testosterone exposure is related to sexually dimorphic facial morphology in adulthood

Abstract: Prenatal testosterone may have a powerful masculinizing effect on postnatal physical characteristics. However, no study has directly tested this hypothesis. Here, we report a 20-year follow-up study that measured testosterone concentrations from the umbilical cord blood of 97 male and 86 female newborns, and procured three-dimensional facial images on these participants in adulthood (range: 21-24 years). Twenty-three Euclidean and geodesic distances were measured from the facial images and an algorithm identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
162
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(172 citation statements)
references
References 57 publications
7
162
1
2
Order By: Relevance
“…While the literature provides a proximate understanding of the pathway through which T affects fundamental frequency via androgen receptors on the vocal folds (Voelter et al, 2008), we have no similar leads on how T might affect fWHR. Moreover, adult fWHR is not associated with either prenatal (Whitehouse et al, 2015) or adult testosterone (Bird et al, 2016). Finally, it's not clear that fWHR is sexually dimorphic (Kramer et al, 2012; Lefevre et al, 2012; Ozener, 2012; Kramer, 2017; however, see Weston et al, 2007; Geniole et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While the literature provides a proximate understanding of the pathway through which T affects fundamental frequency via androgen receptors on the vocal folds (Voelter et al, 2008), we have no similar leads on how T might affect fWHR. Moreover, adult fWHR is not associated with either prenatal (Whitehouse et al, 2015) or adult testosterone (Bird et al, 2016). Finally, it's not clear that fWHR is sexually dimorphic (Kramer et al, 2012; Lefevre et al, 2012; Ozener, 2012; Kramer, 2017; however, see Weston et al, 2007; Geniole et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…There are also as many as seven alternative hypotheses that have been presented to explain the fWHR association with T (see research and discussion by Haselhuhn et al, 2013; Hehman et al, 2015; Whitehouse et al, 2015; Zebrowitz et al, 2015; Eisenbruch et al, 2017; Kramer, 2017). One hypothesis that has been under-examined thus far is that the fWHR-behavior relationships are a byproduct of the association between fWHR and other relevant traits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pubertal androgens may function to activate the expression of secondary sex traits, such as F 0, whereas the nature or magnitude of this masculinization may be predetermined very early in ontogeny [35]. Indeed, researchers have found that the second-to-fourth digit ratio (an index of fetal testosterone exposure [36]) and prenatal serum testosterone levels predict the degree of facial masculinization in pre-pubertal boys [17] and adult men [18,19]. …”
Section: Discussionmentioning
confidence: 99%
“…However, other studies did not observe significant associations between men's basal testosterone and their facial attractiveness, dominance or masculinity (Hönekopp et al 2007;Neave et al 2003;Pound et al 2009). Similarly, studies investigating possible relationships between aspects of facial morphology, such as facial width-to height ratio, and men's testosterone levels have also observed little evidence for correlations between men's facial appearance and testosterone levels (e.g., Whitehouse et al 2015; for a metaanalytic review see Bird et al 2016).…”
Section: Introductionmentioning
confidence: 99%